2001
DOI: 10.1076/ceyr.23.1.38.5424
|View full text |Cite
|
Sign up to set email alerts
|

Hypercholesterolemia induces leukocyte entrapment in the retinal microcirculation of rats

Abstract: Enhanced leukocyte entrapment in the retinal microcirculation was induced in the early stage of hypercholesterolemia. Entrapment was increased as the period of hypercholesterolemia was prolonged. Leukocyte accumulation in the retina may be an early vascular dysfunction leading to arteriosclerosis in hypercholesterolemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 19 publications
0
8
0
1
Order By: Relevance
“…9 Tomida et al showed that hypercholesterolemia itself induces leukocyte accumulation in the rat retina. 18 However, serum lipid levels are unchanged by pitavastatin administration in rats. It has also been reported that pitavastatin prevents NMDA-induced retinal ganglion cell death by suppressing leukocyte recruitment in rats.…”
Section: Discussionmentioning
confidence: 99%
“…9 Tomida et al showed that hypercholesterolemia itself induces leukocyte accumulation in the rat retina. 18 However, serum lipid levels are unchanged by pitavastatin administration in rats. It has also been reported that pitavastatin prevents NMDA-induced retinal ganglion cell death by suppressing leukocyte recruitment in rats.…”
Section: Discussionmentioning
confidence: 99%
“…Chen et al (39) reported that dyslipidemia, not hyperglycemia, induces inflammatory adhesion molecules in human retinal vascular endothelial cells. In fact, leukocyte entrapment in the retinal microcirculation is enhanced in the early stage of hypercholesterolemia even in nondiabetic rats and was increased as the period of hypercholesterolemia was prolonged (6).…”
Section: Fig 5 Linear Regression Analysis Of Polymorphonuclear Leukmentioning
confidence: 96%
“…Leukocyte entrapment in the retinal microcirculation was enhanced in the early stage of hypercholesterolemia even in nondiabetic rats (6). Dyslipidemia has been associated with endothelial dysfunction and impaired vasodilatory response, and postprandial hypertriglyceridemia is exaggerated in type 2 diabetes (7).…”
mentioning
confidence: 99%
“…Conceivably, conformational activity of FPRs and CD18 integrins, both of which have been reported to exhibit shear sensitivity for neutrophils, may be influenced by membrane cholesterol levels that potentially interfere with mechanotransduction processes [138]. Moreover, there is substantial evidence [58,60,[147][148][149] demonstrating a relationship between hypercholesterolemia and enhanced leukocyte activity in the microcirculation. Thus, similar to the case for hypertension, elevated leukocyte activity in the microcirculation may be linked to microvascular dysfunction and impaired tissue perfusion.…”
Section: Impaired Neutrophil Shear Response and Microvascular Dysfuncmentioning
confidence: 99%